Learning war : the evolution of fighting doctrine in the U.S. Navy, 1898-1945 - Hone, Trent (Studies in naval history and sea power., 2018)
"Learning War examines the U.S. Navy's doctrinal development from 1898-1945 and explains why the Navy in that era was so successful as an organization at fostering innovation. Trent Hone argues that the Navy created a sophisticated learning system in the early years of the twentieth century that led to repeated innovations in the development of surface warfare tactics and doctrine. This book draws profoundly important conclusions that give new insight, not only into how the Navy succeeded in becoming the best naval force in the world, but also into how modern organizations can exploit today's rapid technological and social changes in their pursuit of success."--Provided by publisher.